In vivo measurements of lamination patterns in the human cortex. Issue 9 (11th March 2022) - Tomer, Omri; Barazany, Daniel; Baratz, Zvi; Tsarfaty, Galia; Assaf, Yaniv
Abstract: The laminar composition of the cerebral cortex is tightly connected to the development and connectivity of the brain, as well as to function and pathology. Although most of the research on the cortical layers is done with the aid of ex vivo histology, there have been recent attempts to use magnetic resonance imaging (MRI) with potential in vivo applications. However, the high‐resolution MRI technology and protocols required for such studies are neither common nor practical. In this article, we present a clinically feasible method for assessing the laminar properties of the human cortex using standard pulse sequence available on any common MRI scanner. Using a series of low‐resolution inversion recovery (IR) MRI scans allows us to calculate multiple T1 relaxation time constants for each voxel. Based on the whole‐brain T1 ‐distribution, we identify six different gray matter T1 populations and their variation across the cortex. Based on this, we show age‐related differences in these population and demonstrate that this method is able to capture the difference in laminar composition across varying brain areas. We also provide comparison to ex vivo high‐resolution MRI scans. We show that this method is feasible for the estimation of layer variability across large population cohorts, which can lead to research into the links between the cortical layers and function, behavior and pathologies that was heretofore unexplorable. Abstract : In this article, we present a clinically feasible method for assessing the laminar properties of the human cortex based on multicompartment T1 measurements. We identified six different grey matter T1 populations, and we show here their variation across the cortex, as well as their correlation with age.